PKM Pendidikan Internalisasi Nilai-Nilai Tasawuf dalam Pembelajaran Al-Qur’an Sebagai Upaya Penguatan Semangat Belajar Santri - M. Rofiqur Rahman; Ach. Zayyadi; Ilvan Sona Syaifillah; Awan Al Farisi; M. Ardi Firnanda (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Islamic boarding school education plays a strategic role in shaping students who are intellectually superior and spiritually mature, but in practice, learning the Qur'an is often faced with the problem of declining enthusiasm and motivation for students to learn. This PKM research aims to examine the effectiveness of internalizing Sufism values ​​in learning the Qur'an through the study of the book Nurul Burhan as an effort to strengthen the enthusiasm for learning of students in Islamic boarding schools. The method used is descriptive qualitative research with a phenomenological-reflective approach, which relies on participatory observation, students' verbal reflections, activity documentation, and literature reviews as primary and secondary data sources. The results of the discussion indicate that the integration of Sufi values ​​such as sincerity, patience, worship orientation, and purification of the soul in the study of the Qur'an is able to shift the learning patterns of students from mere routine memorization to learning that is spiritually meaningful. The research findings indicate an increase in intrinsic motivation of students characterized by enthusiasm for learning, reflective involvement, and the awareness that learning the Qur'an is part of a spiritual journey to get closer to God. The implications of this research indicate that a learning model based on the internalization of Sufi values ​​has the potential to be a relevant pedagogical alternative for Islamic boarding schools in developing holistic, value-oriented, and sustainable Qur'an learning.